1999
DOI: 10.1128/aem.65.5.1826-1833.1999
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Methanotrophic and Nitrifying Bacteria to CH 4 and NH 4 + Oxidation in the Rhizosphere of Rice Plants as Determined by New Methods of Discrimination

Abstract: Methanotrophic and nitrifying bacteria are both able to oxidize CH4 as well as NH4 +. To date it is not possible to estimate the relative contribution of methanotrophs to nitrification and that of nitrifiers to CH4 oxidation and thus to assess their roles in N and C cycling in soils and sediments. This study presents new options for discrimination between the activities of methanotrophs and nitrifiers, based on the competitive inhibitor CH3F and on recovery after inhibition with C2H2. By usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 50 publications
2
50
0
Order By: Relevance
“…No nitrite was detected, but nitrate was found in millimolar concentrations at low methane source strength, and in particular upon fertilization (Table S2). In previous experiments with soil from this site, nitrification in rhizospheric soil could be ascribed to MOB (Bodelier and Frenzel, 1999). One of the reverse primers used, A682r, co-amplifies the gene of the bacterial ammonium monooxygenase subunit A (amoA).…”
Section: Resultsmentioning
confidence: 98%
“…No nitrite was detected, but nitrate was found in millimolar concentrations at low methane source strength, and in particular upon fertilization (Table S2). In previous experiments with soil from this site, nitrification in rhizospheric soil could be ascribed to MOB (Bodelier and Frenzel, 1999). One of the reverse primers used, A682r, co-amplifies the gene of the bacterial ammonium monooxygenase subunit A (amoA).…”
Section: Resultsmentioning
confidence: 98%
“…Potential methane production activity (PMP) was determined as described by Bodelier et al (2006), while potential methane oxidation activity (PMO) was described by Bodelier and Frenzel (1999). For more details see the Appendix.…”
Section: Experimental Designmentioning
confidence: 99%
“…Numerous studies have shown, using pure cultures, microcosms and field trials, that nitrogen additions decrease methane oxidation (Bedard and Knowles, 1989;Conrad and Rothfuss, 1991). On the other hand, recent rice microcosm studies (Bodelier and Frenzel, 1999;Bodelier et al, 2000) have clearly shown that N fertilization increases methane oxidation in densely rooted rice soil. N limitation of methane oxidation is compatible with the idea that methanotrophs in rhizosphere soil face intense plant and microbial competition for N. The extent to which methane oxidation takes place in plant roots and rhizospheres compared with at the soil-water interface may influence how methane oxidation and methanotroph populations respond to nitrogen additions, an interaction that few studies have focused on thus far (Conrad and Rothfuss, 1991;Van Der Nat and Middelburg, 1998).…”
Section: Effect Of Rice Plants On Methanotroph Populationsmentioning
confidence: 99%